WEBSITE USAHA EKONOMI DESA SIMPAN PINJAM Studi Kasus: UED-SP Lancang Kuning Desa Rumbai Jaya Kecamatan Kempas - Dwi Yuli Prasetyo (Program Studi Teknik Industri, 2018)
Savings and loan village economic business (UED-SP) Lancang Kuning is a rumbai village government-owned business entity in the Kempas sub-district which is engaged in storing and borrowing village community money that serves to help financial management of rural communities, as village-owned enterprises operating at the service level. financial activities that are quite complete and almost similar to banking, the UED-SP Lancang Kuning must implement a computerized (computerized) technology system to help facilitate the performance of the operators / officers, administrators, chairmen, and members of the Lancang Kuning UED-SP, therefore researchers try help facilitate by designing the village economic business website save yellow sassy loan which in this website there are several supporting facilities such as deposit, loan, withdrawal, member and reporting menu, where all menus displayed on this website are daily activities carried out by the operator so it can assisting in facilitating users, not only operators who are helped but members or customers are also helped because the transaction will be more easier and faster, and minimize the occurrence of data input errors that can harm customers or members. This website is built using the Php programming language and MySQL database, using PHP and MySQL can reduce website errors and large data storage, so that it can reduce system development costs (maintenance), the results of the implementation of this website obtained a hypothesis where the business website Savings and loan village economics can help customers in terms of deposits, withdrawals and loans, for operators or officers can help manage deposit, withdrawal, loan input and facilitate reporting, so that with this website can improve the effectiveness of user and system user performance.